Freeze dried plasma and fresh red blood cells for civilian prehospital hemorrhagic shock resuscitation. (June 2015) - Sunde, Geir A.; Vikenes, Bjarne; Strandenes, Geir; Flo, Kjell-Christian; Hervig, Tor A.; Kristoffersen, Einar K.; Heltne, Jon-Kenneth
Abstract : BACKGROUND: The last decade of military trauma care has emphasized the role of blood products in the resuscitation of hemorrhaging patients. Damage-control resuscitation advocates decreased crystalloid use and reintroduces blood components as primary resuscitative fluids. The systematic use of blood products have been described in military settings, but reports describing the use of freeze dried plasma (FDP) or red blood cells (RBCs) in civilian prehospital care are few. We describe our preliminary results after implementing RBCs and FDP into our Helicopter Emergency Medical Service (HEMS). METHODS: We collected data on the use of FDP (LyoPlas N–w (AB)) during a 12-month period from May 31, 2013, to May 30, 2014, before RBC (0Rh (D) negative) introduction in June 2014. FDP and RBCs were indicated in trauma and medical patients presenting with clinical significant hemorrhage on scene. Data were obtained from HEMS registry and patient records. RESULTS: Our preliminary results show that FDP was used in 16 patients (88% males) during the first year. Main patient categories were blunt trauma (n = 5), penetrating trauma (n = 4), and nontrauma (n = 7). Ten patients (62%) were hypotensive with systolic blood pressures less than 90 mm Hg on scene. The majority (75%) received tranexamic acid. Of 14 patients admitted to the hospital, 11 received emergency surgery and 8 needed additional transfusions within the first 24 hours. No transfusion-related complications were recorded. Two of the FDP patients died on scene, and the remaining 14 patients were alive after 30 days. Early results from the recent introduction of RBC show that RBCs were given to four patients. Two patients (one penetrating trauma and one blunt trauma patient) died on scene because of exsanguination, while additional two patients (one blunt trauma patient and one with ruptured aortic aneurism) survived to hospital discharge. CONCLUSION: Our small study indicates that introduction of FDP into civilian HEMS seems feasible and may be safe and that logistical and safety issues for the implementation of RBCs are solvable. FDP ensures both coagulation factors and volume replacement, has a potentially favorable safety profile, and may be superior to other types of plasma for prehospital use. Further prospective studies are needed to clarify the role of FDP (and RBCs) in civilian prehospital hemorrhagic shock resuscitation and to aid the development of standardized protocols for prehospital use of blood products. LEVEL OF EVIDENCE: Therapeutic study, level V.